Nilai-Nilai Kepemimpinan Nabi Yusuf dalam Tafsir Rabbanā Perspektif Trait Theory - Bunga Syalsabilla; Moh Abdul Kholiq Hasan (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
The Indonesian nation is a nation that is predominantly Muslim. However, ironically, the Indonesian state is known for its various crimes which are quite high, one of which is corruption. The weakness of the leader is one indicator of the cause. Among the leadership values that can be used as an example is the leadership of the prophet Yusuf. This research is descriptive qualitative research with primary data in the form of Tafsīr Rabbanā min Kalāmi Rabbinā. Data collection techniques were in the form of literature studies, resource interviews and data analysis using the Trait Theory Psychology approach. Prophet Yusuf's leadership traits are in accordance with the psychological theory of Trait Theory in Tafsīr Rabbanā, reflecting on the six main characteristics of leadership, namely drive and self-confidence, honesty and integrity, leadership motivation, cognitive ability (scientific intelligence ability), emotional calm and firmness (tough- think). These qualities were obtained by the prophet Yusuf externally and internally. But the most important thing is the revelation from Allah as Allah's messenger that no other leader, apart from the prophets, has.